Kātaki ē mamá moe hopohopokia : perceptions and experiences of Tongan male learners in higher education in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Education at Massey University, Albany Campus, New Zealand - Tānaki, 'Olikoni (Massey University, 2015)
Tongans are known as one of the greatest seafaring people, constantly and fearlessly venturing beyond the sunrise in search of new lands and new grounds to conquer and seeking better opportunities away from home. However, settlement and the adjustment and transition into a new life in the new destinations invariably come with sets of unfamiliar challenges and obstacles that demand often rather painful and difficult socio-economic acculturation. Such is the story of the Tongan Aotearoa diaspora. Tongan migrants in Aotearoa New Zealand (A/NZ) have faced quite stringent challenges resulting in their having been largely distracted and diverted from their “New Zealand-the promised-land” dream. The Tongan experience in, and encounters with, the New Zealand education system is a standout example of the most serious of these challenges as evidenced predominantly by the lack of numeracy and literacy skills. As direct result of this gap Tongans along with, and similar to, their fellow Pasifika students are quite conspicuous amongst those seen as failures in the education system in A/NZ. Literature shows a widening gap between policies and practises and the need to address the issue urgently. Responding to concerns about these increasing barriers, this study specifically provides ethnic gender specificity by exploring the experiences of Tongan males at higher education in A/NZ. In my research, and as presented in this thesis, I use the Tongan methodologies of talanoa, tālanga, and tālave with the Kakala framework to provide comfortable space and time where the experiences, perceptions, and voices of Tongan male learners at higher education were unravelled. Makatūkia and makatuʻu were identified and discussed, and various overarching institutions such as kāinga, lotu, self and cosmos were identified to play dual roles in the failures and successes of Tongan male learners. This research also develops and presents a new conceptual framework; Kalia-Langimālie which is grounded on the theoretical orientations of tā-vā kāinga, fashioned by the understanding that vā is mutual, interpersonal, and reciprocal with tā to represent movements, beat, and rhythms. The result of this undertaking empirically concurs that when policies and practises are grounded within, and built on, meaningful values that understand Tongans’ tā-vā through their worlds of self, kāinga, lotu and cosmos, success is attainable.
Keywords: Tongans; Men; Education (Higher); New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education